Pengaruh Penggunaan Aplikasi Tik Tok Terhadap Interaksi Sosial Kelas XI Siswa Di MAS AL- WASHLIYAH Desa Pakam Kecamatan Medang Deras Kabupaten Batu Bara - Kiki Griya Angguri; Maryadi; Kasran (Jurnal Penelitian dan Ilmu-Ilmu Keislaman, 2023)
This study uses a quantitative approach. Where the symptoms will be measured using numbers. This type of research is ex post facto. The data collection technique used is a questionnaire (questionnaire), observation and documentation. The subjects in this study were students of class XI. The results of the research in this thesis, there is the influence of the use of the tik tok application on the social interaction of class XI students. This is evidenced from the table of output coefficients obtained tcount value of 3.690. With= 5%, dk= 59-2=57, the ttable value is 2,000. From these numbers, it can be seen that tcount (3,690) > ttable (2,000), as well as with a significance value of 0.00 < 0.05, it can be concluded that if the hypothesis is accepted, it means that there is an effect of using the tik tok application on the social interactions of class XI MAS students. AL-WASHLIYAH Pakam Village, Medang Deras Subdistrict, Batu Bara Regency for the 2022/2023 Academic Year.